Effect of Solanum lycopersicum Supplementation on Lipid Profile and Atherogenic Indices in Wistar Rats Fed a High-Fat Diet (Sahel Journal of Life Sciences FUDMA, 2026)
This study evaluated the potential of Solanum lycopersicum (tomato) powder supplementation in preventing high-fat diet (HFD)-induced metabolic, hepatic, and renal complications. Diets rich in fat, often associated with increased consumption of junk food, are prevalent and contribute to oxidative stress and chronic inflammation. Nutraceuticals with antioxidant properties have been proposed as accessible and cost-effective strategies for mitigating such effects. Twenty-eight Wistar rats were assigned to four dietary groups: standard diet, HFD, HFD supplemented with 3.5% tomato powder, and standard diet supplemented with 3.5% tomato powder. Growth parameters, glycemic control, lipid profile, and markers of liver and kidney function were assessed using blood glucose monitoring, lipid profiling, and enzymatic assays. Results showed that rats fed tomato-supplemented HFD had higher feed intake and weight gain compared to the unsupplemented HFD group. Serum lipid analysis revealed increased cholesterol, triglycerides, and lipoprotein levels in the supplemented groups. Liver enzyme activities (AST and ALT) were significantly elevated in the supplemented standard diet group, indicating possible hepatic stress. Renal function markers, including urea and creatinine, also showed significant alterations, suggesting potential kidney involvement. Atherogenic indices, including Atherogenic Index of Plasma (AIP), Cardiac Risk Index I (CRI-I), and Cardiac Risk Index II (CRI-II), were evaluated. Although tomato supplementation did not cause a severe electrolyte imbalance, findings indicate limited benefits in weight control and lipid regulation, with possible adverse effects on liver and kidney function. These results highlight the need for further investigation before recommending tomato powder supplementation in high-fat diets.